A comparative study on the electrical and dielectric properties of Al/Cd-doped ZnO/p-Si structures - Buyukbas-Ulusan, A.; Tascioglu, I.; Tataroglu, A.; Yakuphanoğlu, Fahrettin; Altindal, S. (Springer, 2019)
We have reported on the electrical and dielectric properties of Al/CdxZn1-xO/p-Si structures. The cadmium-doped zinc oxide (CdxZn1-xO) thin films with various Cd dopants (x=0.10, 0.20 and 0.30) were deposited on p-Si wafers via sol-gel spin coating method. The admittance (Y=G(m)+i omega C-m) measurements were performed at 1MHz. The C-2-V plots were used to extract the main electrical parameters such as the diffusion potential (V-D), the concentration of acceptor atoms (N-A), depletion region width (W-D) and barrier height (Phi(B)). The experimental results reveal that the capacitance increases with higher Cd dopant concentration due to the presence of interfacial charges while an opposite behaviour is observed in conductance. The lower values of conductance in the sample with high Cd content can be attributed to increase in series resistance. The dielectric measurements also confirm the effect of Cd substitution in ZnO on the device performance.
Keywords: Thin-Films; Frequency; Modulus; Conductivity; Interface; Impedance